If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17c + 6(c + -5c) + -9c = 0 Combine like terms: c + -5c = -4c 17c + 6(-4c) + -9c = 0 Remove parenthesis around (-4c) 17c + 6 * -4c + -9c = 0 Multiply 6 * -4 17c + -24c + -9c = 0 Combine like terms: 17c + -24c = -7c -7c + -9c = 0 Combine like terms: -7c + -9c = -16c -16c = 0 Solving -16c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '-16'. c = 0 Simplifying c = 0
| X-7=28 | | -2(x-3)=x+5-3x | | 2x^2+2y^2=162 | | 15+8x-9(7x-3x)= | | 5.7q-2.8-4.9q=-0.2q-3.4 | | 8*30=12*x | | -4z+z-3(8z+6)= | | 13x+13=5x+5+7x | | -4(a+1)-3a=-7(2a-3) | | 21o-16p+3p+11p-9o= | | 16v^2+8v+1=0 | | 12+9a-6a+7a-15a+5a= | | 2x(x-3)=43 | | x^2-18x+50=0 | | 2x^2+6=8 | | -8y+6y-4y-13y= | | 4(3x+2)+2(5x-6)=5(2x+4) | | -4m+6=9m+31 | | -9b+6b-11b-3b= | | V^2-400=0 | | 10x+8-4+5x= | | 2(7x-3)+4=40 | | 14y+8=-5y+4 | | (-11a-8b)(-5a-6b)= | | -2x+15=9 | | -8-23=-15 | | 4.8x-4=3.8x | | 5x-(2x+6)=15 | | .34(y+3)=4y | | (9c-2d)(3c-7d)= | | y+3=12y | | 5v^2-19v=4 |